Ideals of Immersion in Early Cinema - Holmberg, Jan (Cinémas)

(untitled) (Cinémas, 2003)
AbstractWith the cliché of allegedly “primitive” cinema spectators fleeing the theatre in fear of onrushing train as a point of departures, this article investigates various immersive and stereoscopic strategies in early cinema. Although the three-dimensional or virtual qualities of, for example, phantom rides, Hale’s Tours, and early tracking shots have often been discussed, the notion of a “virtual reality avant la lettre” merits a fuller investigation. Through different technological, textual and discursive strategies, much early cinema can be seen to create a strong sense of presence or immersion that is, with the use of spectacle and engagement radically different than the sense of “identification” crucial to the later classical style.